2014
DOI: 10.1371/journal.pone.0087163
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Cognitive Impairment in Korean ALS Patients without Known Genetic Mutations

Abstract: BackgroundCognitive impairment is associated with a negative prognosis in amyotrophic lateral sclerosis (ALS), as well as with clinical specificity. We investigate neuropsychological function in ALS patients without known genetic mutations in a Korean tertiary clinic.MethodsThree hundred and eighteen patients were enrolled in a prospective longitudinal cohort from September 2008 to February 2012. At the time of diagnosis of sporadic ALS, we carried out genetic and comprehensive neuropsychological tests on all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
2
38
1
Order By: Relevance
“…The frequencies with which they occur in Asian patients with ALS are less clear. In a cohort of 166 South Korean patients with sporadic ALS, 42% of patients were found to have behavioural or cognitive dysfunction 77. None carried the C9orf72 repeat expansion, which accounts for the highest proportion of ALS/FTD overlap in the West, suggesting that a different genetic mutation may be responsible 5.…”
Section: Non-motor Features Of Alsmentioning
confidence: 99%
“…The frequencies with which they occur in Asian patients with ALS are less clear. In a cohort of 166 South Korean patients with sporadic ALS, 42% of patients were found to have behavioural or cognitive dysfunction 77. None carried the C9orf72 repeat expansion, which accounts for the highest proportion of ALS/FTD overlap in the West, suggesting that a different genetic mutation may be responsible 5.…”
Section: Non-motor Features Of Alsmentioning
confidence: 99%
“…A quantitative assessment of strength has, in fact, been included in almost every clinical trial of ALS/MND. Multiple measures of strength have been repeatedly utilized in this patient population ranging from classic categorical measurement (manual muscle testing), comprehensive composite measures of strength (Tufts Quantitative Neuromuscular Exam [71,72]) and focused quantitative evaluation of individual muscle groups (hand-held dynamometry [73]). Despite the logic of utilizing strength as a measure of disease activity in a motor neuron disease, the variability between patients with regard to affected regions, baseline strength, and rate of progression has offset the practical utility of strength measurements in clinical trials.…”
Section: Biomarkersmentioning
confidence: 99%
“…It is well known that clinical manifestations and specific demographic characteristics such as age at onset can serve as useful predictors [32,33]. However, recent longitudinal studies suggest that cognitive and behavioral decline - though found to be mild and asynchronous with motor decline by some researchers [34,35] - are also evident in a proportion of patients and may be crucial prognostic indices with regard to the course of the disease [34,36,37]. Contemporary research provides indications for a possible biological substrate of the suggested relationship between cognitive/behavioral decline and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent research reports a possible link between specific genetic abnormalities, cognitive and behavioral impairment, and reduced survival [39] . On the basis of such findings demonstrating parallel motor and cognitive decline, along with the latter's possible prognostic value, it has been argued that clinicians should use screening tools to identify subtle cognitive/behavioral deficits and classify ALS patients according to assessment-derived neuropsychological profiles [36]. …”
Section: Discussionmentioning
confidence: 99%